Case Report: Management of Malignancy-Exacerbated Pemphigus Vulgaris During COVID-19 Pandemic - Corrà, Alberto; Cammelli, Francesca; Quintarelli, Lavinia; Barbato, Giuseppe; Le Rose, Ornella; Salemme, Adele; Di Zenzo, Giovanni; Coratti, Francesco; Verdelli, Alice; Aimo, Cristina; Mariotti, Elena Biancamaria; Bianchi, Beatrice; et al. (Frontiers in Medicine, 2021)
Pemphigus Vulgaris is an intraepidermal autoimmune mucocutaneous blistering disease whose etiopathogenesis includes various trigger factors, i.e. drugs and malignancies. We present a case of malignancy-exacerbated pemphigus vulgaris which required a careful diagnostic process in order to rule out paraneoplastic pemphigus, along with the challenges posed by the need of treating both cutaneous and oncologic diseases. Possible post-operative complications postponed the start of first-line immunosuppressive treatment of pemphigus. Moreover, the infective risks had to be minimized during the peak of COVID-19 pandemic in Italy. Intravenous immunoglobulins were chosen as “bridge” therapy before the tumour surgical excision, followed by rituximab in post-operative phase.